In Vivo Tracking of Chemokine Receptor CXCR4-Engineered Mesenchymal Stem Cell Migration by Optical Molecular Imaging - Senthilkumar Kalimuthu; Ji Min Oh; Prakash Gangadaran; Liya Zhu; Ho Won Lee; Ramya Lakshmi Rajendran; Se hwan Baek; Yong Hyun Jeon; Shin Young Jeong; Sang-Woo Lee; Jaetae Lee; Byeong-Cheol Ahn (Hindawi Limited, 2017)
CXCR4, the stromal cell-derived factor-1 receptor, plays an important role in the migration of hematopoietic progenitor/stem cells to injured and inflamed areas. Noninvasive cell tracking methods could be useful for monitoring cell fate. Therefore, in this study, we evaluated the efficacy of an intravenous infusion of genetically engineered mesenchymal stem cells (MSCs) overexpressing CXC chemokine receptor 4 (CXCR4) to home to the tumor, by optical imaging. We constructed a retroviral vector containing CXCR with dual reporter genes, eGFP and Fluc2, under the control of an EF1α promoter (pBABE-EF1α-CXCR4-eGFP-IRES-Fluc2). We also developed an eGFP-Fluc2 construct in the Retro-X retroviral vector (Retro-X-eGFP-Fluc2). MSCs were transduced with retroviruses to generate CXCR4-overexpressing MSCs (MSC-CXCR4/Fluc2) and MSCs (MSC/Fluc2). CXCR4 mRNA and protein expression was confirmed by RT-PCR and Western blotting, respectively, and it was higher in MSC-CXCR4/Fluc2 than in naive MSCs. eGFP expression was confirmed by confocal microscopy. The transfected MSC-CXCR4/Fluc2 cells showed higher migratory capacity than naive MSCs observed in Transwell migration assay. The in vivo migration of CXCR4-overexpressing MSCs to MDAMB231/Rluc tumor model by BLI imaging was also confirmed. Intravenous delivery of genetically modified MSCs overexpressing CXCR4 with a Fluc2 reporter gene may be a useful, noninvasive BLI imaging tool for tracking cell fate.